1988
DOI: 10.1126/science.241.4868.951
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Symbiotic Dinitrogen Fixation by a Toxin-Releasing Plant Pathogen

Abstract: An approximate doubling in plant growth, total plant nitrogen, nodulation, and overall dinitrogen fixation of alfalfa are the consequences of the action of a toxin delivered by a Pseudomonas infesting the alfalfa rhizosphere. The toxin, tabtoxinine-beta-lactam, inactivates selectively one form of glutamine synthetase in the nodules. Thus, normal glutamine synthetase-catalyzed ammonia assimilation is significantly impaired; yet these plants assimilated about twice the normal amount of nitrogen. How plants regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…Therefore, we have shown that the increase in α-amino-nitrogen in bacteroids correlates with a decrease in nitrogenase activity (Mendoza et al, 1995). Knight & Langston-Unkefer (1988) have found that the glutamate and glutamine content of nodules affects nitrogenase activity. The nitrogen assimilated into amino acids in the bacteroids may contribute to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have shown that the increase in α-amino-nitrogen in bacteroids correlates with a decrease in nitrogenase activity (Mendoza et al, 1995). Knight & Langston-Unkefer (1988) have found that the glutamate and glutamine content of nodules affects nitrogenase activity. The nitrogen assimilated into amino acids in the bacteroids may contribute to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…In legumes, an accumulation of Asn was observed when GS activity was impaired, suggesting that other enzymes (e.g., Asn synthetase) may be important in bypassing the flux of reduced nitrogen to avoid a toxic accumulation of NH 4 þ , thus ensuring plant survival (Carvalho et al, 2003;Harrison et al, 2003;Wong et al, 2004). The question as to whether these alternative metabolic pathways are important in the control of plant productivity has been extensively studied in legumes and nonlegumes (Knight and Langston-Unkefer, 1988;Brears et al, 1993;Lam et al, 2003) but has still not been fully elucidated, particularly in cereals.…”
Section: Physiological Impact Of Decreased Gs Activitymentioning
confidence: 99%
“…mate in GS biosynth were found between GS1a and GS1d. ATP is known to be an allosteric effector of plant GS (33). Therefore, the K m value for ATP could not be determined.…”
Section: Fig 4 Sds-page Of Gs Purified From Maize Rootsmentioning
confidence: 99%